Medical abortion through telehealth in India: a critical perspective - Dipika Jain; Anubha Rastogi; Kavya Kartik; Anmol Diwan; Oieshi Saha (Sexual and Reproductive Health Matters, 2022)
The COVID-19 pandemic and nationwide lockdowns have significantly impacted access to abortions for millions of people in India. One of the proposed solutions to address the inaccessibility of abortion services is the use of teleconsultation or “telemedicine” where pregnant persons consult with Registered Medical Practitioners (RMPs) over voice or video calls. The RMPs then prescribe the necessary medication electronically. However, telehealth services bring their own set of social and legal challenges. Although they can allow for greater access to medical abortions, especially in situations where pregnant persons are unable to opt for in-person medical care, it is important to note that telemedicine is not a one-stop solution for lack of access to timely, affordable abortions. This is particularly due to the structural barriers of caste, class, religion, gender, and disability that impede access to healthcare services. In this article, we examine the need for telehealth services in India as a means of increasing access to medical abortion services and the structural barriers that prevent it from being an effective and equitable solution for all.